1997
DOI: 10.1002/(sici)1096-911x(199710)29:4<296::aid-mpo11>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Dural sinus thrombosis in children with cancer

Abstract: p h o b la s tic ly m p h o m a ; tw o B urkitt's ly m phom a), etiology rem ained unknow n. In these children, DST occurred early in the course of therapy. The m edian interval betw een start of chem otherapy an d onset of symptoms w as 19 days (range 8-40). No child had received Lasparaginase. Prognosis was favourable, with sym ptom s c o m p le te ly disap p earin g w ith o u t therapy within 1 to 5 days. The incidence of DST in p atien ts w ith ad v an ced stage non-H odgkin lym phom a during induction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…During pregnancy or puerperium, a significant increase in the risk of cerebral venous thrombosis was associated with caesarian delivery (OR 3.1), increasing maternal age (OR 2.5), presence of comorbidities including hyperhemesis (OR 14.2), intercurrent infections (OR 3.45) and maternal hypertension [18] Neurosurgery [19] Meningitides [20] Arterovenous malformation [21] Sepsis (sinusitis, mastoiditis, cellulitis) [22,23] Stroke and hemorrhage Space-occupying lesions Jugular catheterization Systemic Dehydration (diabetic ketoacidosis) Septicemia [24] Pregnancy and puerperium [5] Inflammatory bowel disease [25] Malignancy [26] Sarcoidosis [27] Collagen disease (Behcet's syndrome, SLE, Sjögren's syndrome) [28][29][30] Homocysteinuria [31] Nephrotic syndrome [32] Autoimmune thyroiditis Drugs…”
Section: Etiologymentioning
confidence: 99%
“…During pregnancy or puerperium, a significant increase in the risk of cerebral venous thrombosis was associated with caesarian delivery (OR 3.1), increasing maternal age (OR 2.5), presence of comorbidities including hyperhemesis (OR 14.2), intercurrent infections (OR 3.45) and maternal hypertension [18] Neurosurgery [19] Meningitides [20] Arterovenous malformation [21] Sepsis (sinusitis, mastoiditis, cellulitis) [22,23] Stroke and hemorrhage Space-occupying lesions Jugular catheterization Systemic Dehydration (diabetic ketoacidosis) Septicemia [24] Pregnancy and puerperium [5] Inflammatory bowel disease [25] Malignancy [26] Sarcoidosis [27] Collagen disease (Behcet's syndrome, SLE, Sjögren's syndrome) [28][29][30] Homocysteinuria [31] Nephrotic syndrome [32] Autoimmune thyroiditis Drugs…”
Section: Etiologymentioning
confidence: 99%
“…Kyrnetskiy et al identified 51 children with cancer and intracranial hemorrhages, which included subdural, epidural, subarachnoid and intracerebral (parenchymal or intraventricular) hemorrhages, in an 18-year retrospective review and found 30 children with brain tumors, 19 with leukemia and 2 with lymphoma 12 . There is literature focusing on stroke in children with selected neoplasms (either leukemia, specifically ALL, or brain tumors) 13–15 , or characterizing single stroke type (intracerebral hemorrhage, ischemic stroke or cerebral sinovenous thrombosis (CSVT) in children with cancer 12, 16, 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this was not considered in patient A while under our care. Previous reports have described a variety of thrombotic events in children with disseminated neuroblastoma [13,14]. These studies demonstrate that a minority of children with neuroblastoma develop a poorly characterized prothrombotic state with increased platelet-aggregating activity as a result of excess thrombin production from the tumor and are at risk from venous occlusion at a variety of sites [15].…”
Section: Discussionmentioning
confidence: 86%